2017
DOI: 10.1027/1618-3169/a000371
|View full text |Cite
|
Sign up to set email alerts
|

Risk Preferences in Surrogate Decision Making

Abstract: Abstract. There is growing evidence that decisions made on behalf of other people differ from the decisions we make for ourselves because we are less affected by the subjective experience of their outcome. As a result, the decisions we make for other people can be more optimal. This experiment investigated surrogate decision making using a probability discounting task where participants made choices between risky and sure options. Psychological distance between the decision maker and the recipient was manipula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 37 publications
0
31
0
1
Order By: Relevance
“…It has been found that people's surrogate predictions are closer to risk neutrality than the decisions they make for themselves, both in the domain of gains where people were risk averse but predicted someone else to be less risk averse as well as in the domain of losses where people were risk seeking and predicted that someone else would be less risk seeking (Faro & Rottenstreich, 2006;Hadar & Fischer, 2008;Hsee & Weber, 1997;Krishnamurthy & Kumar, 2002). Research has also shown that people's surrogate choices are closer to risk neutrality than the decisions they make for themselves in both gain and loss frames (Batteux, Ferguson, & Tunney, 2017;Sun, Liu, Zhang, & Lu, 2016;Zhang, Liu, Chen, Shang, & Liu, 2017;Ziegler & Tunney, 2015). Such findings suggest that perhaps in a financial context people make surrogate decisions in accordance with their predictions of what that person would do: they predict that person's risk preferences and choose accordingly.…”
Section: Surrogate Decisions and Predictions Involving Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that people's surrogate predictions are closer to risk neutrality than the decisions they make for themselves, both in the domain of gains where people were risk averse but predicted someone else to be less risk averse as well as in the domain of losses where people were risk seeking and predicted that someone else would be less risk seeking (Faro & Rottenstreich, 2006;Hadar & Fischer, 2008;Hsee & Weber, 1997;Krishnamurthy & Kumar, 2002). Research has also shown that people's surrogate choices are closer to risk neutrality than the decisions they make for themselves in both gain and loss frames (Batteux, Ferguson, & Tunney, 2017;Sun, Liu, Zhang, & Lu, 2016;Zhang, Liu, Chen, Shang, & Liu, 2017;Ziegler & Tunney, 2015). Such findings suggest that perhaps in a financial context people make surrogate decisions in accordance with their predictions of what that person would do: they predict that person's risk preferences and choose accordingly.…”
Section: Surrogate Decisions and Predictions Involving Riskmentioning
confidence: 99%
“…There are findings suggesting that people are less risk averse for others than for themselves (Batteux et al, 2017;Mengarelli, Moretti, Faralla, Vindras, & Sirigu, 2014;Pollmann, Potters, & Trautmann, 2014;Polman, 2012), while others showing that people are more risk-averse for others (Eriksen & Kvaly, 2010;Fernandez-Duque & Wifall, 2007;Zaleska & Kogan, 1971), as well as findings reporting no self-other differences (Benjamin & Robbins, 2007;Stone, Yates, & Caruthers, 2002). These findings concerning surrogate choices have been discussed relative to the Risk-as-Feelings hypothesis (Batteux et al, 2017;Fernandez-Duque & Wifall, 2007), reduced loss aversion (Mengarelli et al, 2014;Polman, 2012), increased caution due to responsibility (Zaleska & Kogan, 1971), and Social Values Theory (Stone & Allgaier, 2008). However, there has been little mention of the interplay between surrogate predictions and surrogate choices.…”
Section: Surrogate Decisions and Predictions Involving Riskmentioning
confidence: 99%
“…However, in the financial domain, the literature is rather contradictory. There are findings suggesting that decision-makers are less risk averse for close and distant recipients [13,19,3236], while others reporting that decision-makers are more risk averse for recipients [37,38], as well as findings reporting no self-other differences [39,40]. The aim of the meta-analysis will be two-fold: firstly, identifying whether self-other differences vary across domains and why that may be the case, and secondly, examining whether certain factors can explain the discrepancies in the financial domain.…”
Section: Introductionmentioning
confidence: 99%
“…An optimal decision-maker would be indifferent between the risky and sure option in our study as they both have the same expected value. People show more indifference for others and could therefore be considered to be more optimal, which there is a precedent for in risky choice (Batteux et al, 2017), intertemporal choice (Ziegler & Tunney, 2012) and information search (Liu, Polman, Liu, & Jiao, 2018). Similarly to the risk-as-feelings account, this has been explained by the presence of an empathy gap (Loewenstein, 1996), whereby people are emotionally removed from the outcome of the decision in a surrogate context.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, their risk preferences would be more risk neutral for others. Indeed, when choosing between sure and risky options, people who are risk-averse for themselves are less so for others, whereas those who are risk-seeking are less so for others (Batteux, Ferguson, & Tunney, 2017;Eriksen, Kvaløy, & Luzuriaga, 2014). Similarly, because decision-makers tend to be riskaverse for gains they should take more risk for others, and vice versa for losses (Tversky & Kahneman, 1981).…”
mentioning
confidence: 99%